Clinical Study of Paliperidone Palmitate Long-Acting Injection Combined With Electroacupuncture in the Treatment of Methamphetamine Addicts - Yu Chen; Mingchao Li; Qiuming Ji; Zou Su; Ziyu Yang; Yin Xu; Qian Chen; Dan Liao; Jihua Zeng; Yuhong Yang (Frontiers Media S.A., 2021)
Objective: To explore the clinical efficacy of paliperidone palmitate long-acting injection combined with electroacupuncture in the treatment of methamphetamine addicts.Methods: This study focused on methamphetamine addicts who were admitted to our hospital from January 2020 to December 2020 as the main research object, with a total of 89 cases. The patients were divided into a control group of 45 cases and a study group of 44 cases according to the treatment method. The control group was treated with electroacupuncture, and the study group was treated with paliperidone palmitate long-acting injection on the basis of electroacupuncture in the control group. After 6 months of continuous treatment, the treatment effect of methamphetamine withdrawal symptom score before and after treatment was used; Hamilton Anxiety Scale score and Hamilton Depression Scale were used to compare the anxiety and depression situation of the two groups; the brain wave α and θ wave situation of the two groups were compared.Result: The results showed that there was no significant difference in the scores of Ma withdrawal symptoms, Hamilton Anxiety and Hamilton Depression between the two groups before treatment (p < 0.05); after 3 and 6 months of treatment, the scores of Ma withdrawal symptoms, Hamilton Anxiety and Hamilton Depression in the study group were significantly lower than those in the control group and the difference was statistically significant (p < 0.05); 6 months after the completion of the treatment, the α wave amplitude and Fourier transformed α brain wave (FFTα) in the study group were significantly higher than those in the control group, and the difference was statistically significant (p < 0.05).Conclusion: Paliperidone palmitate long-acting injection combined with electroacupuncture is better than electroacupuncture alone in the treatment of methamphetamine addicts, and can significantly improve anxiety, depression and brain waves, thereby preventing addicts from relapse.